UJIAN NASIONAL DALAM KONSEP EVALUASI PENDIDIKAN - Muhammad Idrus (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2010)
Evaluation is the one of several important activities to increase the quality of education. The national examination is the technique in evaluate education process. Today, debating about pro and contra national examination still in progress. Some experts, like teacher and politician doubt the effectiveness of national examination, but on the other side many experts believe the national examination is the best solution for increasing the quality of education. Despite the weakness especially in practice, the national examination was good solution for many problem to increase the quality of education, and in conceptual’s context the national examination was the effective way for increasing quality. Besides that, the national examination was a mandate from constitution (UU No. 20/2003 and PP No. 19/2005). So, it is unfair if national examination must be cancelled only based on several doubt from some expert without give chance to government for reduction the weakness.